A Voronoi Approach for Coverage Protocols in Wireless Sensor Networks - Boukerche, A.; Xin Fei (IEEE GLOBECOM 2007 - IEEE Global Telecommunications Conference, 2007)
The Voronoi Diagram(VD) is a fundamental algorithm for resolving the coverage problems of wireless sensor networks. Most VD based coverage algorithms collect global location information and construct a VD using a centralized construction algorithm. However, the collection process of global location information is expensive and can not be guaranteed in all scenarios. Based on a localized VD construction algorithm this paper proposes a region coverage algorithm and a fully sponsored coverage algorithm where the GPS requirement for global location awareness is removed. The performance of such algorithms is evaluated by the complexity and message cost through a set of simulation experiments. The results show that our algorithms are better in both aspects when they are compared to the centralized region coverage algorithms and central angle algorithm. The performance and flexibility of our algorithms make them a potential solution for regional coverage and off- duty applications.